How does meditation relate to quality of life, positive lifestyle habits and carbon footprint? - E.A.S.K. Somarathne; M.W. Gunathunga; E. Lokupitiya (Heliyon)
There is increasing scientific interest in the potential links between meditation practice and pro-environmental behaviours. The present research investigates relationships between Vipassana meditation experience (temporal variables of meditation, five facets of trait mindfulness), positive lifestyle habits (PLH), quality of life (QoL) and per-head carbon footprint (CF) among 25 skilled meditators. Self-reported validated questionnaires were given to a group of native speakers of Sri Lanka to collect data on meditation experience, PLH, and perceived QoL. In estimating CF four domains (food and beverage consumption, electricity consumption, traveling and solid waste disposal) were considered. Correlation analyses revealed that trait mindfulness showed strong associations (r > 0.4) with PLH. None of the temporal variables of meditation experience was significantly correlated with any domain of CF. Two facets of mindfulness (observing and non-reactivity to present-moment experience) demonstrated statistically strong associations (p < 0.05) with perceived QoL. It was found that the PLH significantly mediates the relationship between the observing facet of trait mindfulness and CF associated with food and beverage consumption (indirect effect - 0.002, SE = 0.001 95 % CI [0.010, 0.417]). Further, the relationship between acting with awareness and CF associated with solid waste disposal at landfill sites was significantly mediated by the PLH (indirect effect – (−0.003), SE = 0.003 95 % CI [-0.012, −0.0001]). The current study will serve as a foundation for future longitudinal studies on the same subject by providing evidence for the relationships between meditation experience and PLH, perceived QoL and CF.